1972
DOI: 10.1002/ijc.2910100308
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long‐term exposure to DDT on CF‐1 mice

Abstract: CF-I minimal inbred mice were given technical DDT mixed into the diet atThe main reasons for the concern regarding the potential hazard for human health represented by DDT are based on (a) its ubiquity, (b) its persistence in the environment, (c) its capacity to accumulate in living organisms, including man, and its capacity to accumulate in the foetus and in mothers' milk and (d) the experimental evidence of its ability to increase tumour incidence in laboratory animals.The experimental evidence of the carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

1973
1973
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(30 citation statements)
references
References 14 publications
(10 reference statements)
3
26
1
Order By: Relevance
“…It should be noted, however, that the doses of o,p 0 -DDT used in the present study were significantly higher than those administered with the technical grade DDT. Exposure to technical grade DDT at doses as low as 0.26 mg DDT/kg/day produced liver tumors in mice [Tomatis et al, 1972;Thorpe and Walker, 1973]. Increases in pulmonary adenomas and malignant lymphomas also were seen in mice at doses ranging from 1-32.5 mg/kg/day [Kashyap et al, 1977].…”
Section: Discussionmentioning
confidence: 93%
“…It should be noted, however, that the doses of o,p 0 -DDT used in the present study were significantly higher than those administered with the technical grade DDT. Exposure to technical grade DDT at doses as low as 0.26 mg DDT/kg/day produced liver tumors in mice [Tomatis et al, 1972;Thorpe and Walker, 1973]. Increases in pulmonary adenomas and malignant lymphomas also were seen in mice at doses ranging from 1-32.5 mg/kg/day [Kashyap et al, 1977].…”
Section: Discussionmentioning
confidence: 93%
“…However, in the investigation of Tomatis et al (1972) in DDT-treated CF-I mice the most frequent types of tumours were not only lung tumours, but also lymphomas, osteomas and, especially, hepatocellular liver tumours. This difference may depend on the various strains of mice used and on the more prolonged time span of the experiments of Tomatis et al We used mice of strain A, which were very susceptible to lung blastomogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Similar well-differentiated and moderately well-differentiated carcino mas, such as those described here, were reported in CF1 mice by T omatis et al [21] and Walker et al [22], Similar small carcinomas have been observed in rats ingesting dieldrin and aldrin [4,5]; however, one study using rats was described as being negative [23], The carcinomas also de veloped from hyperplastic parenchymal cells adjacent to central veins. A few moderately well-differentiated carcinomas were described in rats receiving subcutaneous injections of another organochlorine chemical, carbon tetrachloride [13].…”
Section: Discussionmentioning
confidence: 59%